Role Play Method for Social Emotional and Cognitive Development of 4-5 Years Old Children at Paud Amelia 1 Nedam, Sarmi district, Sarmi Regency - Simanjuntak, Ria Imelda; Latuhihin, Julita Lilian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Role Play method is one of the important methods to be applied in the teaching process, especially for early childhood. It is very helpful for children to develop social emotional and cognitive during their growth. The purpose of this research is to find out how the role of the Role Play method in the social emotional and cognitive development of Early Childhood. The method used is descriptive qualitative with data processing techniques through observation and interviews using teachers as respondents. With the application of this Role Play method, it really helps children to appear confident in front of their friends, children dare to show the ability to collaborate in the classroom, help peers, this also helps children be confident in their abilities, and be able to show self-control and patience, besides that children are able to manage their emotions and are able to imagine and create. In using this method, there are several things that need to be considered so that it can be right on target, one of which is that the teacher must prepare himself and prepare what is needed before using this method. It should also be noted that the Role Play method has supporting factors and inhibiting factors.